AI in academic writing: Concerns, classroom strategies, and pedagogical insights - Wakerkwa, Dian Agustina Purwanto; Pertiwi, Sri Ananda; Indriyani, Novi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
The growing presence of artificial intelligence (AI) in education has brought new opportunities and challenges to the teaching of academic writing. While AI tools can enhance learning and support both teachers and students, their use also raises concerns related to authenticity, creativity, and academic integrity. Guided by the AI literacy framework, this study explored English lecturers’ experiences in addressing issues in AI-assisted writing classes. Employing a qualitative case study design, data were collected through classroom observations and semi-structured interviews with three English lecturers from two Indonesian universities. The observations examined how AI tools were integrated into classroom instruction, while the interviews provided insights into participants’ perceptions, concerns, and instructional strategies in relation to critical, ethical, and pedagogical dimensions of AI literacy. The findings revealed three main themes: the benefits of AI, concerns surrounding its use, and strategies for responsible integration. Participants noted that AI supports personalized learning, enhances engagement, and assists in material preparation and feedback provision. However, they also expressed concerns about plagiarism, reduced creativity, loss of authorial voice, and cultural bias in AI outputs. The study highlights practical strategies to address the concerns and to maintain responsible and ethical use of AI to preserve authenticity and academic integrity.